2012
DOI: 10.1002/app.38871
|View full text |Cite
|
Sign up to set email alerts
|

The potential of flavonoids as natural antioxidants and UV light stabilizers for polypropylene

Abstract: This paper presents a study on the stabilization of polypropylene (PP) against thermo-oxidation and UV radiation by using natural phenolic compounds derived from structures of flavonoids: a flavone (chrysin), a flavanol (quercetin), two flavanone glycosides (hesperidin and naringin) and flavanoligand (silibinin). Thermal stabilization has been assessed in an oxidizing atmosphere by means of differential scanning calorimetry (DSC) both in isothermal as well as dynamic conditions. In addition, the effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
77
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 25 publications
(33 reference statements)
10
77
1
2
Order By: Relevance
“…antioxidants, plasticizers, fillers, etc. [7][8][9][10]. With the increasing development of nanotechnology, many research works have been focused of using nanostructures to improve the properties of PLA-based materials [11][12][13] and interactions.…”
Section: Introductionmentioning
confidence: 99%
“…antioxidants, plasticizers, fillers, etc. [7][8][9][10]. With the increasing development of nanotechnology, many research works have been focused of using nanostructures to improve the properties of PLA-based materials [11][12][13] and interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The compound is a flavonol type flavonoid, which has proven antioxidant, antiviral and anti-inflammatory effect in the human body. Some research groups have attempted already to use quercetin as an antioxidant in polyolefins [12,13], while others tried to apply it as a component of active packaging material [14][15][16][17]. In the latter case mostly the migration and dissolution of the antioxidant was studied in various solvents modeling food.…”
Section: Introductionmentioning
confidence: 99%
“…The authors did not find any aggregates in the polymer, stability increased considerably, while oxygen permeation decreased simultaneously. Samper et al [13] studied the thermo-and photooxidative stabilization of polypropylene (PP) with different flavonoids and found that flavonol type compounds, like quercetin, are the most efficient antioxidants. Lopez de Dicastillo and co-workers [15] stabilized successfully an ethylene vinyl alcohol copolymer with quercetin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another by-product antioxidant obtained from olive processing, hydroxytyrosol (3,4-dihydroxy-phenylethanol), was found to offer good melt stability to PP [4]. Different flavonoids such as chrysin, hesperidin, naringin and quercetin were also considered as possible natural phenolic antioxidants and UV-stabilisers for PP [5]. Quercetin was found to be effective in stabilising PP against thermal oxidation and UV radiation, and against oxidation in PE melt.…”
Section: Introductionmentioning
confidence: 99%